Postcard from Marianne Homburger to Max Bredig, December 3, 1939 - Homburger, Marianne (1939)
Postcard from Marianne Homburger (1903-1986) and Viktor Homburger (1888-1968) to Max Albert Bredig (1902-1977). Marianne tells Max that she is worried about their father, Georg Bredig (1868-1944). She believes that his travels were hard on him and is not sure he is being taken care of. She ends the letter telling Max that their number for immigrating to the United States won't be called for at least another two years.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Homburger, Viktor, 1888-1968; Jewish Holocaust (1939-1945); Emigration and immigration; Refugees; Jewish refugees; World War (1939-1945); Third Reich